2011
DOI: 10.1038/nature10664
|View full text |Cite
|
Sign up to set email alerts
|

Response to self antigen imprints regulatory memory in tissues

Abstract: Immune homeostasis in tissues is achieved through a delicate balance between pathogenic T cell responses directed at tissue-specific antigens and the ability of the tissue to inhibit these responses. The mechanisms by which tissues and the immune system communicate to establish and maintain immune homeostasis are currently unknown. Clinical evidence suggests that chronic or repeated exposure to self antigen within tissues leads to an attenuation of pathologic autoimmune responses, possibly as a means to mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
248
5
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(264 citation statements)
references
References 16 publications
6
248
5
5
Order By: Relevance
“…Much, albeit not all, of the dampened signaling in Treg cells could be ascribed to their higher proportion of CD44 hi effector/ memory cells (28)(29)(30). Signaling cascades are less readily activated via the TCR in such cells (27), and this distinction also applies to Treg cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much, albeit not all, of the dampened signaling in Treg cells could be ascribed to their higher proportion of CD44 hi effector/ memory cells (28)(29)(30). Signaling cascades are less readily activated via the TCR in such cells (27), and this distinction also applies to Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to TCR engagement are known to be less intense in memory than in naïve T cells (27), and this could be an important confounder, as a significant fraction of Treg cells have a memory phenotype (28)(29)(30). We used the expression of CD44 and CD62L molecules to distinguish between naïve and memory phenotypes during the response to CD3/CD28 cross-linking.…”
Section: Significancementioning
confidence: 99%
“…Indeed, T regs are detected within tolerant grafts (3,5,50), indicating alloreactive T regs could be recruited to or even retained at sites of alloantigen expression and actively participate in tolerance induction or maintenance. Rosenblum et al (52) found self-Ag expression in skin resulted in T regs that are activated, more potent suppressors and maintained within skin, which offered subsequent protection when self-Ag is re-expressed. Joffre et al (25) demonstrated that T regs expanded in vitro with directly or indirectly presented donor antigens prevents both acute and chronic rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion peaks around the first month after HSCT and appears to contract by activation-induced cell death (AICD). It still remains unclear whether some part of graft-derived Treg would survive or not as functionallymemory suppressor cells for a long time after HSCT [26].…”
Section: Phase 1: Expansion Of Graft-derived Tregmentioning
confidence: 99%